Hubungan Perdarahan dan Partus Lama pada Ibu Post Partum dengan Kejadian Infeksi pada Masa Nifas - Sulastri, Sulastri; Putri, Amelia; Rahmah, Rahmah; Haryanti, Dwi (Universitas Nurul Jadid, 2024)
Postpartum infection is an infection occurring after childbirth up to 42 days postpartum, characterized by fever, pelvic pain, foul-smelling lochia, and subinvolution of the uterus (delayed return of the uterus to its pre-pregnancy state). The leading causes of maternal mortality in Indonesia include hemorrhage, hypertensive disorders during pregnancy, infections, and metabolic disorders, with 25-50% of maternal deaths related to pregnancy, childbirth, and the postpartum period. This study aims to determine the relationship between hemorrhage and prolonged labor in postpartum mothers with the incidence of postpartum infections. The research used an analytical method with a retrospective approach. The population consisted of all postpartum women with infections, totaling 30 respondents in 2022. The sampling technique used total sampling with 30 respondents. Data analysis was performed using the chi-square test. The results showed a significant relationship between hemorrhage (p=0.03) and prolonged labor (p=0.04) with the incidence of postpartum infections at H. Abdul Manap Hospital, Jambi City, in 2023. The conclusion of this study is that there is a relationship between hemorrhage and prolonged labor with the incidence of postpartum infections at H. Abdul Manap Hospital, Jambi City.